2017
DOI: 10.1088/1361-6528/aa5bad
|View full text |Cite
|
Sign up to set email alerts
|

Radiation effects on GaAs/AlGaAs core/shell ensemble nanowires and nanowire infrared photodetectors

Abstract: With the recent advances in nanowire (NW) growth and fabrication, there has been rapid development and application of GaAs NWs in optoelectronics. It is also of importance to study the radiation tolerance of optoelectronic nano-devices for atomic energy and space-based applications. Here, photoluminescence (PL) and time-resolved photoluminescence measurements were carried out on GaAs/AlGaAs core/shell NWs at room temperature before and after 1 MeV proton irradiation with fluences ranging from 1.0 × 10-3.0 × 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 61 publications
0
22
0
Order By: Relevance
“…Due to the crystallographic structure the cross section of such wires is usually hexagonal [1][2][3][4][5][6][7], but other shapes like triangles [8][9][10][11][12][13][14] or dodecagons [15] have already been obtained. These radial heterojunctions have been in the focus of extensive experimental [4][5][6][7][16][17][18][19][20][21] and theoretical [22][23][24] studies in the recent years. This is mostly due to the possibility of controlling some of their physical properties, e.g., the band alignment.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the crystallographic structure the cross section of such wires is usually hexagonal [1][2][3][4][5][6][7], but other shapes like triangles [8][9][10][11][12][13][14] or dodecagons [15] have already been obtained. These radial heterojunctions have been in the focus of extensive experimental [4][5][6][7][16][17][18][19][20][21] and theoretical [22][23][24] studies in the recent years. This is mostly due to the possibility of controlling some of their physical properties, e.g., the band alignment.…”
Section: Introductionmentioning
confidence: 99%
“…Afterward, Li et al carried out 1 MeV proton and H + irradiation experiments on GaAs/AlGaAs core-shell NWs at room temperature and found that the minority carrier lifetime is closely related to the irradiation-induced defect density by photoluminescence (PL) method. In addition, the size dependence of the carrier lifetime damage factor of GaAs NWs is mainly attributed to a special dynamic mechanism of defect annihilation, as summarized by them [14,15]. These results generally indicate that NW is a better candidate structure for radiation resistance.…”
Section: Introductionmentioning
confidence: 90%
“…This constraint is overcome by the core-shell nanopillar structure. Core-shell p-n junction embedded within the nanopillar structure allows orthogonalization of the photon absorption and carrier collection direction [12,13]. Owing to this the minority carriers travel a shorter path length as compared to the minority diffusion length.…”
Section: Introductionmentioning
confidence: 99%